El ideal estético en jóvenes de Medellín: percepciones desde algunas prácticas de estética corporal (2011)
ABSTRACT: The article is result of an investigation that had the purpose of identifying the perceptions about the aesthetic ideal they have some youths of both sexes in the city of Medellín in 2009, and that they adopt certain practices of corporal aesthetics. The results allowed to establish that the consumption culture constituted in a important factor to inclination of the massive media where the practices of corporal aesthetics that the youths adopt in the study, allow to evidence a “to model the body” adjusted to the aesthetic models that the society of consumption contemporary imposes through the products, the diets, the practices and routines of exercises or, the incorporation or adoption of extreme measures to obtain the aesthetics ideal that is yearned with persistence.